Reverse genetic, proteomic and physiological approaches to uncover the role of rice chloroplastic APXS in drought and light responses. - Cunha, Juliana Ribeiro da (2018)
Reactive oxygen species (ROS) production is common to plant aerobic metabolism, but when this production reaches excessive levels, e.i. abiotic stress, important processes such as photosynthesis are strongly impaired. To combat the excess of ROS, plants have an extensive antioxidant defense system, with the ascorbate peroxidase (APX) enzymes playing an important role throughout the cell. In order to understand the role of APX chloroplast isoforms (chlAPXs) and its performance for the maintenance of photosynthetic efficiency in rice plants (Oryza sativa L.) under conditions of moderate drought and excess light, this thesis used an integrative approach, evaluating genetic, proteomic, biochemical and physiological aspects. For this, rice plants were silenced (RNAi) individually for the stromal APX (sAPX - apx7 plants) and thylakoidal (tAPX - apx8 plants) isoforms of APX and their photosynthetic and growth performances were evaluated under normal conditions and moderate drought stress. apx7 plants presented a proteomic profile very similar to NT plants, although they present a slight increase in the accumulation of H2O2 under normal growth conditions. On the other hand, the tAPX silencing led to intense proteomic alteration as well as growth reduction and greater accumulation of H2O2 when compared to NT and apx7 plants. Interestingly, apx7 plants showed an intense increase in APX cytosolic isoform activity (cAPX) and little change in total chlAPX activity. On the other hand, tAPX silencing triggered a reduction in the activity of cAPX and sAPX, reducing the total activity of chlAPX. Probably, such changes occurred due to the silencing process, since apx7 and apx8 plants presented approximately 50% and 90% reduction in the transcripts of OsApx7 and OsApx8, respectively. Probably as a result of these and other genetic, biochemical and physiological changes, apx7 plants presented a morphological phenotype similar to NT plants. However, apx7 plants exhibited better growth performance, photosynthetic efficiency and stress indicators in response to moderate drought. The partial reduction of OsApx7 transcripts appears to induce post-transcriptional and post-translational changes, allowing for a more efficient gene-protein-metabolic arrangement to cope with the stress of drought. However, it was not possible to establish a cause and effect relationship between the proteome and the phenotype. On the other hand, apx8 plants showed lower ability to increase protein abundance in response to drought, especially proteins involved in photosynthesis, redox metabolism and stress response when compared to NT plants in the same condition. In fact, apx8 plants showed higher membrane damage, lower relative water content and lower photosynthesis values, while apx7 plants maintained high levels of Rubisco carboxylation (Vcmax) and gas exchange parameters. In addition, apx8 plants showed an increase in photorespiration in relation to NT, especially after drought stress, indicating a greater dissipation of excess energy. Therefore, it was investigated which other possible mechanisms of photoprotection would have been triggered by apx8 plants in situations of moderate and high electron pressure (moderate and high light). apx8 plants have an increase in the cyclic electron flow and NPQ, mainly in situations of high pressure of electrons, probably as a way to dissipate energy in the compensation of the unbalance caused to the water-water cycle with the silencing of tAPX, avoiding or minimizing the photoinhibition of the photosystem I. The results obtained in this thesis are important to understand the function of chlAPXs and their role in regulation of photosynthesis.